Draft Genome Sequence of Komagataeibacter intermedius Strain AF2, a Producer of Cellulose, Isolated from Kombucha Tea - Correa dos Santos, Renato Augusto; Berretta, Andresa Aparecida; Barud, Hernane da Silva [UNESP]; Lima Ribeiro, Sidney Jose [UNESP]; Gonzalez-Garcia, Laura Natalia; Zucchi, Tiago Domingues; Goldman, Gustavo H.; Riano-Pachon, Diego M. (Amer Soc Microbiology, 2015)
Here, we present the draft genome sequence of Komagataeibacter intermedius strain AF2, which was isolated from Kombucha tea and is capable of producing cellulose, although at lower levels compared to another bacterium from the same environment, K. rhaeticus strain AF1.